Custo-efetividade de duas coberturas na prevenção de úlcera por pressão sacral - Inoue, Kelly Cristina (2014)
The prevention of pressure ulcers (PU) is an indicator of nursing care quality to be considered by the nurse who works in health institutions, mainly when this professional is responsible for the care of patients restricted to hospital bed. It is known that despite the major part of PU prevention actions be considered like simple and easy application, some of them might need some type of investment from the institutions, including financial support, such as the situation of protect dressings used in bony prominences, which have been specially used in sacral region, local recognized as the highest incidence of PU. Due to the need of improving the practices of intensive care, with higher quality and safety of care, associated to the rational use of resources to the organizational survival, it is necessary to do researches in the Pharmaceutical and economics area, because these studies can help in decision by choice of resources which have more effectiveness and also economic viable. This study, a controlled clinical trial, had as general objective to analyze the relation cost-effectiveness of dressings in prevention of sacral PU, was conducted in the period from 2013 October to 2014 March, in an ICU for adults (ICUA) of a private hospital of Paraná, Brazil. Among the 80 patients evaluated for eligibility, 31 were excluded or did not receive allocation because they didn?t attend the pre-established criteria (minimum age of 18 years, do not have PU on ICU-A admission and to be unable to active mobilization in the bad in the admission?s moment), two for the impossibility of realizing the evaluation to the in the ICU-A toward to these criteria and five for not having less than 24 hours of hospitalization at the ICU-A. Therefore, 17 patients were allocated in control group (CG); 15 in intervention group of transparent film (IGF) and 10 in intervention group of hydrocolloid (IGH); totalizing 42 participants. The patients allocated in one of the intervention groups (IGF or IGH) were submitted to fixation of dressings on standard way by the nurse staff, after doing skin hygiene with clorhexidina solution in gauze, followed by drying it with gauze. The data were collected daily by the patient observation and his medical record, using a semi-structured instrument and afterwards they were compiled and organized in electronic reports, for descriptive and inferential statistical analysis, through the computer program R, SPPS 20 (Statistical Package for the Social Sciences) and EpiInfoTM 7. The ethical and legal aspects were obeyed, with favorable approval of the Ethics Committee of Research of Faculdade Ingá, from Maringá, Paraná, Brazil, number 262.314/2013, CAAE number 3426113.4.0000.5220. Among the results it was verified that: there is no significant difference among the effectiveness in the three groups (CG, IGH and IGF) in prevention of sacral PU, and the transparent film is a more cost-effective strategy than the hydrocolloid sheet. After all, the conclusion was that it is necessary develop new researches with enlarged samples which can be statistically representative, considering that was a limitation in the present study.